Microclimate, development and productivity of robusta coffee shaded by rubber trees and at full sun - Araújo, André; Partelli, Fábio; Oliosi, Gleison; Pezzopane, José Ricardo (Revista Ciência Agronômica, 2016)
There are few studies about the shading of Robusta coffee with rubber trees. The aim of this study was evaluate the microclimate, development and yield of Coffea canephora grown at full sun and shaded by rubber trees. The experiment consisted of a Robusta coffee crop (Coffea canephora) grown at under full sun and another coffee crop intercropped with rubber trees (Hevea brasiliensis). The rubber trees and coffee crop were planted in the East/West direction, in Jaguaré, Espírito Santo, Brazil. Was evaluated the luminosity, temperature and relative humidity, leaf nutrient concentrations; internodes of the plagiotropic and orthotropic branches, leaf area; relative chlorophyll index, and tree yield of the coffee crops. The shading directly influenced the microclimate by reducing the air temperature in the summer and winter, as well as by increasing relative humidity. Luminosity in the summer had an average decrease of 905 lumens ft-2 throughout the day, which was equivalent to 72.49%, and luminosity in the winter had an average decrease of 1665 lumens ft-2, which was equivalent to 88.04%. The shading provided greater etiolation of the plagiotropic and orthotropic branches as well as greater leaf expansion as compared to the full sun. The leaf concentration of Fe and Mn were higher in the shaded coffee. Estimated chlorophyll b and total chlorophyll were greater in the coffee crop grown at under full sun. The dense shading produced by rubber trees provided losses in the coffee crop yield, however, there is the formation of the rubber tree.